1997
DOI: 10.7326/0003-4819-126-4-199702150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Determining Course and Outcome of Diabetic Patients Who Have Had Acute Myocardial Infarction

Abstract: In the thrombolytic era, mortality rates of diabetic patients who have had acute myocardial infarction remain 1.5 to 2 times higher than those in nondiabetic patients. This increased mortality rate is caused by diverse mechanisms that affect myocardial function and blood supply and by the tendency toward thrombosis in diabetic patients. Current therapies for myocardial infarction are effective in these patients. Improved metabolic control may also decrease mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
190
0
6

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 0 publications
3
190
0
6
Order By: Relevance
“…Diabetic patients are at increased risk of cardiovascular disease and their prognosis after acute events is poorer than that of non-diabetic subjects [13]. The present study demonstrates that ischaemia-and growth factor-mediated mobilisation of progenitor cells is defective in diabetic rats.…”
Section: Discussionmentioning
confidence: 52%
“…Diabetic patients are at increased risk of cardiovascular disease and their prognosis after acute events is poorer than that of non-diabetic subjects [13]. The present study demonstrates that ischaemia-and growth factor-mediated mobilisation of progenitor cells is defective in diabetic rats.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, abciximab, a platelet glycoprotein IIb/IIIa inhibitor, was found to improve outcomes in diabetic patients after percutaneous transluminal coronary angioplasty (25). These observations suggest that hyperglycemia-induced platelet hyperaggregation and the subsequent release of PDGF may be one of the potential causes of the high frequency rates of restenosis in patients with diabetes (26,27). Inhibition of hyperglycemia-induced mitochondrial ROS overproduction may provide a new therapeutic strategy for the treatment of diabetic patients with acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…While advances in PTCA like DES reduce some of these side effects so much so that in many patients with 1-or 2-vessel disease there may be hardly any difference between the two approaches, but for multivessel CAD, the difference may become crucial. In this subgroup, CABG is not only associated with fewer recurrent events or need for re-intervention but also better survival and thus studies after studies consistently demonstrated the superiority of CABG over PTCA, use of DES notwithstanding [4,5]. Similarly, in other situations of profoundly virulent atherosclerosis, CABG may be the best option.…”
Section: Effect Of Diabetes Mellitusmentioning
confidence: 98%